Statistical methods & data analysis - Muhammad, Faqir; Dawood, Hassan (Faisalabad : Kitab Markaz, 2018)
A comprehensive introduction to statistical methods and data analysis, covering descriptive and inferential statistics with examples and applications across multiple disciplines.
In English
Keywords: Statistics; Mathematical statistics; Statistics -- Methodology; Statistics -- Data processing; Research -- Statistical methods